2021
DOI: 10.1111/ijlh.13728
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of white blood cell parameters for COVID‐19: Is there a role for HFLC and IG?

Abstract: Introduction As the Coronavirus disease 2019 (COVID‐19) pandemic is still ongoing with patients overwhelming healthcare facilities, we aimed to investigate the ability of white blood cell count (WBC) and their subsets, high fluorescence lymphocyte cells (HFLC), immature granulocyte count (IG), and C‐reactive protein (CRP) to aid diagnosis of COVID‐19 during the triage process and as indicators of disease progression to serious and critical condition. Methods We collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…It releases large amounts of reactive oxygen species that damage cellular DNA and destroy viruses. Furthermore, NEU can be activated by inflammatory factors linked to the presence of viruses, such as interleukin-6 and interleukin-8, tumor necrosis factor alpha, granulocyte colony stimulating factor and interferongamma, produced by lymphocytes and endothelial cells [24][25][26]. On the other hand, systemic inflammation, triggered by SARS-CoV-2, significantly depresses cellular immunity, leading to a decrease in CD3 + T cells, CD4 + T cells, and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…It releases large amounts of reactive oxygen species that damage cellular DNA and destroy viruses. Furthermore, NEU can be activated by inflammatory factors linked to the presence of viruses, such as interleukin-6 and interleukin-8, tumor necrosis factor alpha, granulocyte colony stimulating factor and interferongamma, produced by lymphocytes and endothelial cells [24][25][26]. On the other hand, systemic inflammation, triggered by SARS-CoV-2, significantly depresses cellular immunity, leading to a decrease in CD3 + T cells, CD4 + T cells, and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of standard blood tests performed upon patient admission to the hospital for the diagnosis and prediction of the severity of COVID-19 infection ( 15 , 22 24 ). The IG% is a metric that is poorly understood and underutilized by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The IG% is a metric that is poorly understood and underutilized by clinicians. In a routine blood count, this parameter may be measured inexpensively and swiftly ( 22 ). The early release of immature neutrophils from bone marrow into peripheral blood has been linked to inflammation, particularly in numerous infectious diseases ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…69 While eosinopenia was identified as a prospective screening, diagnostic and prognostic tool, the true role of eosinophils in lung pathology pursuant this infection is unclear. 72 Eosinopenia was shown to be an early convenient diagnostic and screening tool for COVID-19 infection 73,74 and as a prognostic marker of disease severity and unfavourable outcome in patients with COVID-19 pneumonia. 75,76 Interestingly, eosinophilia (especially in asthmatic patients treated with inhaled corticosteroids) was associated with improved COVID-19 outcome.…”
Section: Eosinophils As Part Of Innate Immunitymentioning
confidence: 99%